The Implementation of the Think Pair Share Strategy through Assemblr Edu Augmented Reality to Enhance Student’s Speaking Skills - Mauizatul Fitrah; Konder Manurung; Andi Patmasari; Hastini Hastini (MASI Mandiri Edukasi, 2026)
Speaking skills are among the most essential components of English language learning; however, many EFL students still struggle to speak fluently and accurately due to limited opportunities for meaningful practice and the reliance on conventional teaching methods. This condition was also found among eleventh-grade students of SMAN 4 Palu, who often hesitated, paused frequently, and lacked confidence when speaking English. Therefore, this research aimed to investigate whether the implementation of the Think-Pair-Share (TPS) strategy through Assemblr Edu Augmented Reality could enhance students’ English speaking skills, particularly in terms of fluency and accuracy. This study employed a quantitative, quasi-experimental design with an experimental and a control group. The population consisted of eleventh-grade students of SMAN 4 Palu, and two classes were selected through simple random sampling. The experimental group was taught using the Think-Pair-Share strategy supported by Assemblr Edu Augmented Reality, while the control group received conventional instruction. Data were collected through oral pre- and post-tests focusing on speaking fluency and accuracy, and were analyzed using SPSS version 29 with descriptive statistics, normality and homogeneity tests, and an independent-samples t-test. The results showed a statistically significant improvement in students' speaking performance in the experimental group compared to the control group. The findings indicate that integrating the Think-Pair-Share strategy with Assemblr Edu Augmented Reality effectively enhances students’ speaking skills by providing structured interaction and visual and audio support.